2019
DOI: 10.3390/app9091921
|View full text |Cite
|
Sign up to set email alerts
|

Development of Pant-Type Harness with Fabric Air-Pocket for Pain Relief

Abstract: Harnesses can be used in various applications, such as entertainment, rescue operations, and medical applications. Because users are supported on the harness for a long time, they should feel comfortable wearing the harnesses. However, existing commercial harnesses are uncomfortable to wear and cause continuous serious pain. Therefore, in this study, a new pant-type harness with a fabric air pocket to reduce the applied pressure on the body, especially in the groin, is proposed. Keeping this in mind, we have d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In Nam's study, the pressure caused by harnesses was measured in different areas of the waist and thighs using a pressure gauge sensor. It was concluded that an optimal harness design could overcome the existing harness limitations and lead to user comfort [ 15 ]. Lee et al evaluated the pressure on people's bodies when using commercial harnesses and found that the pressure caused by harnesses made people uncomfortable, in such a way that they were not willing to use harnesses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Nam's study, the pressure caused by harnesses was measured in different areas of the waist and thighs using a pressure gauge sensor. It was concluded that an optimal harness design could overcome the existing harness limitations and lead to user comfort [ 15 ]. Lee et al evaluated the pressure on people's bodies when using commercial harnesses and found that the pressure caused by harnesses made people uncomfortable, in such a way that they were not willing to use harnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the harness design should help them feel comfortable and satisfied. However, commercially available harnesses cause discomfort as well as severe and persistent pain for end-users [ 15 ]. In addition, users should be mentally evaluated to determine their willingness or unwillingness for wearing harnesses [ 16 ], because harnesses may be present in the workplace but may not be used properly due to dissatisfaction and discomfort) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, qualitative studies could be used in interviews and software. Therefore, it is necessary to identify the critical factors and take corrective and preventive measures [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%